Transformasi Tatanan Hukum dan Demokrasi: Analisis Perubahan Struktural Pasca Reformasi - Azhari, Wildan Habib; Sidiq, Rasyid; Lubis, Fauziah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine the transformation of the level of law and democracy after the Indonesian reformation, of course after independence Indonesia experienced many structural changes from the pre-Reformation era to the post-reformation era. At all times, Indonesia has always tried to develop and improve Indonesia’s structural order, so this research uses two problem formulations, namely how the legal order in post-reformation Indonesia is and how democracy is implemented in post-reformation Indonesia. This research is qualitative research with a normative juridical approach. The results of this research show that the legal order in Indonesia after the 1998 reform, Indonesia experienced significant changes in its legal order and democratic system. The following are the main points related to several things, namely the constitution, government system, elections and political parties, legal developments, human rights protection, and regional autonomy. Overall, post-reform, Indonesia has moved towards a more mature democratic system with improvements in the legal order, more open elections, and increased protection of human rights.